Elevation of intraocular pressure due to ciliary body and iris cysts ”pseudoplateau iris” – case report - Modrzejewska, Monika; Cyrankiewicz, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Iris and ciliary body cysts constitute a significant diagnostic problem and are difficult to diagnose in routine practice on slit lamp or gonioscopy examination. The diagnosis must be established by ultrabiomicroscopy, which is not widely available, but represents the only technique capable of evaluating the anatomical relationships of the visualized ocular structures. Diagnosing ocular hypertension and pseudoplateau iris secondary to iridociliary cysts can be challenging for ophthalmologists, as it is rarely possible to perform a complete diagnostic workup. The authors of this article present a rare case of a patient with bilateral pseudoplateau iris and ocular hypertension associated with iridociliary cysts. In addition, various forms of intraocular pressure-regulating therapies recommended in treatment are reviewed.